First report of natural infection of Xerolenta obvia (Pulmonata, Mollusca) by Dicrocoeliidae (Digenea) larval stages in Turkey - ISMAIL, Fatma Mohamed Abdualrazig Khalifa; GÜRELLİ, Gözde (Kastamonu University, 2018)
Aim of study: This study aimed to investigate the prevalence and morphological features of Dicrocoeliid larval stages (sporocysts and cercariae) in the terrestrial snail Xerolenta obvia (Menke, 1828) inhabiting Kastamonu. Material and Methods: X. obvia samples were gathered after rainfall in the surrounding areas of the Kastamonu province over the spring (i.e. April and May) and autumn (i.e. October and November) of 2016. The samples were dissected alive, and their hepatopancreata were removed and placed into glass tubes containing a 0.6% NaCl solution. The hepatopancreas was dissected using a needle and liquid was spread on a slide as a thin layer, to investigate the parasites' live larval stages. Dicrocoeliid larval stages (sporocysts and cercariae) were examined under a compound microscope, fixed in 5% formalin and stained with Semichon's acetocarmine. The samples were also prepared for observation under a scanning electron microscope. Main results: This was the first report of X. obvia as an intermediate host in the life cycle of the Dicrocoeliidae family in Turkey. In Kastamonu, the infection prevalence was 0.78%, with its highest occurrence in April. Research highlights: Since the snails were gathered mainly from pastures surrounding the villages and farms, where herbivorous animals graze, it was concluded that the larval stages found in the snails might belong to Dicrocoelium dendriticum. The presence of larval stages of this trematode parasite in the snails gathered from the pastures poses a risk to the definitive host animals.
Keywords: 3. Good health